Generative AI and multi-source intelligence for automated security triage - Herris, Fhatur Robby Tanzil; Saragih, Hondor; Anindito, Anindito (Institute of Computer Science (IOCS), 2025)
Security Operation Center (SOC) analysts encounter significant delays due to